2011 Third International Workshop on Quality of Multimedia Experience 2011
DOI: 10.1109/qomex.2011.6065707
|View full text |Cite
|
Sign up to set email alerts
|

Subjective quality assessment of scalable video coding: A survey

Abstract: Scalable video coding is a promising solution for efficient video content distribution to users having heterogeneous network and terminal capabilities. Thanks to its inherent multidimensional adaptability, a scalable bit stream can be used to simultaneously transmit multiple video sequences having different bit rates to corresponding target users, without necessity of re-encoding or transcoding. In order to exploit such an advantage effectively, it is crucial to understand the effects of multidimensional scala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…This is particularly effective in our case where two different quality factors (i.e., coding and packet loss artifacts) exist simultaneously in each stimulus and thus assigning a score for each stimulus is not easy for subjects. By simplifying the subjects' task, the reliability of the results can be significantly enhanced [16,17].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly effective in our case where two different quality factors (i.e., coding and packet loss artifacts) exist simultaneously in each stimulus and thus assigning a score for each stimulus is not easy for subjects. By simplifying the subjects' task, the reliability of the results can be significantly enhanced [16,17].…”
Section: Methodsmentioning
confidence: 99%
“…If the ratio of such violations among all possible triads exceeds a certain threshold, the subject is considered as an outlier. When a tie is included in the rating scale as in our case, the transitivity violation can be examined as follows [17]. Let S i → S j mean that S i is preferred to S j by a subject, and let S i ↔ S j indicate a tie between …”
Section: Data Processingmentioning
confidence: 99%
“…This is particularly effective in our case where two different quality 1358 factors are involved simultaneously and thus assigning a score for each stimulus is not easy for subjects. By simplifying the subjects' task, the reliability of the results can be enhanced [11], [12].…”
Section: Methodsmentioning
confidence: 99%
“…Several research works have investigated the subjective video quality of SVC [17]- [21]. For instance, Politis et al measured the effect of user mobility and handover on the objective and subjective video quality of SVC and H.264/AVC codecs using two CIF video sequences, and reported that SVC outperforms H.264/AVC in both objective and subjective video qualities [17].…”
Section: Impact Of Different Layering Configurations In Svcmentioning
confidence: 99%